From Flower to Honey Bouquet: Possible Markers for the Botanical Origin of Robinia Honey. (12th November 2014) - Aronne, Giovanna; Giovanetti, Manuela; Sacchi, Raffaele; De Micco, Veronica
Abstract : Flowers are complex structures devoted to pollinator attraction, through visual as well as chemical signals. As bees collect nectar on flowers to produce honey, some aspects of floral chemistry are transferred to honey, making chemical markers an important technique to identify the botanical and geographical origins of honey. We applied a new approach that considers the simultaneous analysis of different floral parts (petals, stamens + pistils, calyxes + nectarines, and nectar) and the corresponding unifloral honey. We collected fresh flowers of Robinia pseudoacacia L. (black locust), selected five samples of Robinia honey from different geographical origins, applied SPME-GC/MS for volatile analyses, and defined the chemical contribution added by different floral parts to the honey final bouquet. Our results show that honey blends products from nectar as well as other flower parts. Comparing honey and flower profiles, we detected compounds coming directly from flower parts but not present in the nectar, such as hotrienol and β -pinene. These may turn out to be of special interest when selecting floral markers for the botanical origin of honey.